NB3Sn Targets Synthesis via Liquid Tin Diffusion for Thin Films Depositions - Zanierato, Matteo; Azzolini, Oscar; Cavazzani, Jonathan; Chyhyrynets, Eduard; Diaz, Vanessa Garcia; Glisenti, Antonella; Keppel, Giorgio; Ragazzo, Nico; Stivanello, Fabrizio; Pira, Cristian (Diffusion Fundamentals, 2022)
The deposition of superconducting Nb3Sn on copper accelerating cavities is interesting for the higher thermal conductivity of copper compared to common Nb substrates. The better heat exchange would allow the use of cryocoolers reducing cryogenic costs and the risk of thermal quench [1]. The magnetron sputtering technology allows the deposition of Nb3Sn on substrates different than Nb, however the coating of substrates with complex geometry (such as elliptical cavities) may require target with non-planar shape, which are difficult to realize with classic powder sintering techniques. In this work, the possibility of using the Liquid Tin Diffusion (LTD) technique to produce sputtering targets is explored. The LTD technique is a wire fabrication technology, already developed in the past at LNL for superconducting radio frequency (SRF) applications [2], that allows the deposition of very thick and uniform coating on Nb substrates even with complex geometries [3]. Improvements in LTD process, proof of concept of a single use LTD target production, and characterization of the Nb3Sn film coated by DC magnetron sputtering with these innovative targets are reported in this work.